MOTIONAL INDUCTION VOLTAGE MEASUREMENTS IN ESTUARINE ENVIRONMENTS: THE RIA DE AVEIRO LAGOON (PORTUGAL) - Nolasco R.; Soares A.; Monteiro Santos F.A.; Represas P.; Dias J.M.; Vaz N.; Palshin N.A. (My University, 2006)
Electromagnetic fluctuations in the ocean have external sources like ionospheric-magnetospheric current systems, and purely internal oceanic sources associated with interaction between water velocity fields and the geomagnetic field, that is, the motionally induced voltage (MIV). During the last decade techniques based on MIV have proven to provide reliable information when applied to the flow monitoring at large oceanic channels. In this paper analysis of data resulting from the implementation of these techniques in a small-scale system, that is, the Ria de Aveiro lagoon (Portugal), is presented. A submarine cable crossing the channel at the entrance of the lagoon (Barra channel) allows the measurement of the potential difference between two electrodes located on both sides of the channel. Spectral analysis of these data reveals that measured voltages are dominated by semidiurnal M2, S2/K2 frequencies. Comparison between the sum of the four main constituents determined by harmonic analysis and the sea surface elevation measured at a tide gauge located at the lagoon mouth reveal that the measured potential difference is proportional to the water flow. To estimate the water flow in this location from the MIV measurements the data collected using this methodology were compared with numerical results obtained from a previously calibrated hydrodynamic model. A value of 720 m3 s-1 mV-1 was estimated for the coefficient relating voltage and water transport at Barra. Taking this value into account a sediment layer of about 20 m is estimated, at Barra. The results show that it is possible to indirectly measure the water transport (by tidal and residual flows) through the channel by measuring the differences of electrical potential. This demonstrates the applicability of the MIV method to a small-scale system. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ELECTROMAGNETIC; MOTIONALLY INDUCED ELECTRIC FIELD; SUBMARINE CABLES; TIDES